COVID-19 Pandemic – Do our Indian Nursing Students Have Knowledge about it and Do they Follow Preventive Practices Against It? (Medico Legal Update, 2021)
Introduction: COVID-19 stands for Coronavirus Disease 2019 which is a disease declared as global pandemicon 11th of March, 2020 by the World Health Organization, caused by the newly identified Coronavirus(SARS CoV-2 virus). There is a report of more than 213.6 million confirmed cases of COVID-19 andmore than 4.4 million associated deaths globally, according to Johns Hopkins University.(25.08.2021).Thepresent study has the objectives to assess the prevailing knowledge and known information amongst studentnurses about the COVID-19 pandemic, the known preventive practices against acquiring and spread of thedisease and to learn the preventive practices being used amongst student nurses amidst the pandemic.Thesetting selected for the study was AIIMS, New Delhi, Nurses Hostel through online mode. A convenientnon-probability sampling was adopted for data collection using a structured questionnaire for 2nd year BSc.(Hons) Nursing Students (n=75).The data were obtained and analysis was done in terms of descriptive andinferential statistics. Results showed that 64%, 33.3% ,2.7% nursing students had high, moderate and lowlevel of knowledge (with a score of 18 or more,12-17 and ,lower than 11)respectively. The mean knowledgescore was 17.82 for a total score of 24 (74.25%). 57.3%, 40% and 2.7% had high, moderate and low level ofperformance of preventive practice respectively with a score of 52 or more, 35-51 and lower than 35, and amean of 51.90 for a total score of 70(74.1%). CONCLUSION: A majority of the study population of nursingstudents had adequate knowledge who followed adequate preventive practices against the COVID-19pandemic, however quite a large percentage still had below average knowledge about the disease and aneven lower percentage implemented practices for the prevention of acquiring the disease in their daily lives.